1C.005 Using online parenting discussion forums for understanding fall injury mechanisms in infants. (14th March 2021) - Cooray, Nipuna; Sun, Si; Adams, Susan; Keay, Lisa; Nassar, Natasha; Brown, Julie
Abstract : Background: Falls are the most common mechanism of injury in infants and may result in traumatic brain injuries. Most previous studies fail to focus on fall types specific to infants who are mostly not independently mobile, and lack contextual information vital to development of preventive interventions. Online parenting forums provide an unobtrusive rich data source where infant fall incidents are commonly discussed. The aim of this study was to evaluate online parenting forums to gain insight into events leading to infant falls. Method: Fall incident discussions on an Australian parenting website were identified and downloaded using site-specific google search queries and a programming script. A qualitative descriptive approach was used to analyse and categorise contextual information into 'pre-cursor events' and 'influencing factors' for infant falls. Results: Of the 461 infant fall incidents identified, common mechanisms were falls from furniture and when being carried or supported by someone, falls from baby products and falls on the same level. Common precursor events were infant rolling off or left alone on furniture, product misuse, adults falling asleep while holding the infant; and tripping/slipping while carrying the infant. Common influencing factors were rapid infant motor development, lapses in caretaker attention and trip hazards. Discussion and Conclusions: This study provides insight into parental behaviours preceding infant falls. Findings will help define target behaviours requiring modification and inform development of targeted interventions to prevent falls in infants. Learning Outcomes: Online parenting forums can be utilised to explore child injury scenarios that are vital for intervention development.